Blood Relation - Ben Hagai, Noa (Israel, 2009)
In the early 1940s, 14-year-old Pnina disappeared nearby her house in what is now Israel. Years later, she started sending letters to her family. It turned out that she had married an Arab and had children with him, but it is never completely clear if she ran away or was kidnapped. Director Noa Ben-Hagai found her great-aunt Pnina's letters and asked her uncle, a retired colonel in Israeli intelligence, to find the unknown family in the Palestinian Territories. "Blood Relation" chronicles the various meetings between members of this Jewish-Arab family over the course of three years in both Israel and Nablus. Needless to say that these reunions do not go smoothly: the Arabs ask their family for help to get work permits, and the Israelis feel used. Conversations with family members from both sides illustrate how difficult it can be to bring people from such different and conflicting backgrounds together.
Duration: 01:15:00
Keywords: Documentary films